The q-analogue of the e2;1-transform and its applications - Salem, Ahmed; Uçar, Faruk (My University, 2016)
In this paper, we introduce a new integral transform qe2;1, which is the q-analogue of the e2;1-transform and can be regarded as a q-extension of the e2;1-transform. Some identities involving qL2-transfom, qL2-transfom, and Pq-transform are given. By making use of these identities and qe2;1-transform, a new Parseval-Goldstein type theorem is obtained. Some examples are also given as an illustration of the main results presented here. © TÜBITAK.
Keywords: qL2-transfom; qL2-transfom; Pq-transform; Q-analogue of e2;1-transform; q-Exponential integral